Digitalisasi Ekonomi SIA: Transformasi Sistem Informasi Akuntansi Dalam Meningkatkan Efisiensi Dan Inovasi Bisnis - Angelina Wijaya Tan; Nathalie Elshaday Betrix Ambouw; Irda Agustin Kustiwi (Jurnal Mutiara Ilmu Akuntansi, 2024)
Economic digitalization has changed the business landscape drastically by playing a central role in the transformation of accounting information systems (AIS). This study explores the impact of digitalization on AIS, analyzes emerging challenges and opportunities, and understands the implications for efficiency, transparency and innovation in business operations. Using qualitative and quantitative approaches, this study provides an in-depth analysis of how companies can face these changes successfully. Key words: economic digitalization, accounting information systems, business efficiency, transparency, innovation.